Textualidades problemáticas e desviantes: a formação de um multiverso discursivo em torno do acontecimento jornalístico Casais de O Boticário - José Antônio Ferreira Cirino (2019)
This doctorate thesis had as main focus to research which discursive positioning and problematic fields journalism made emerge surrounding the propaganda Casais de O Boticário, launched on 2015, which brought along homosexual couples exchanging gifts on Valentines Day. The research aimed at perceiving how the LGBTQ issue has been approached on the news considering the discussion of aspects related to sexuality, gender, homosexualities, homophobia and affective setting of couples. For that, the coverage of the main Brazilian online news portals at that time (Estadão, Folha, G1, O Globo, Terra, R7, UOL) was examined along with data gathering directed to the text excerpts with references to the propaganda. After undertaking a mapping of the content of 81 identified news, the research was narrowed down to 13 representative texts of the main facts associated to this event. This work is featured then as a qualitative research theoretically grounded on critical analysis of discourse and methodologically applied out of three-dimensional analysis of discourse by evaluating the texts, the discursive and social practices. By means of an exam of social practice re-contextualization, a critical reading of texts has been done to identify aspects related to consumption, to citizenry, to politics and to religion as the main discursive universes engaged by journalism. This has resulted on what we called discursive multiverse of the propaganda Casais de O Boticário: sociolinguistics criterion of the text excerpts which enables us to understand them as textual materials inserted on the disputes of society sense, on the evaluation of political agenda and the visibilities established along with the propaganda event, as well as on the elucidation of problematic fields which were structured from the resignification work promoted by journalism.